Nilai Kearifan Lokal Batang Haring dalam Pariwisata dan Budaya Kalimantan Tengah - Ni Nyoman Ayu Wilantari; Made Safitri (Tampung Penyang, 2024)
Indonesia's rich natural and cultural resources make tourism a strategic sector for the economy. However, challenges in environmental preservation and local culture need to be faced. The potential of Batang Haring values as local wisdom of Dayak people in Central Kalimantan can be used as a foundation for sustainable tourism development. This research uses the literature method to explore the philosophy of Batang Haring, which includes harmonizing the relationship between humans, God, and nature. These values are expected to be integrated in tourism practices, thus not only attracting tourists but also maintaining cultural and environmental sustainability. The results show that by applying the values of Batang Haring, Central Kalimantan tourism can develop sustainably, provide economic benefits, and preserve local cultural identity.